Performance of HDTMA-Br-Modified Indonesian Zeolite as a Drug Carrier Candidate for Diclofenac Sodium - Khafidhotun Naimah; Harjono Harjono; Jumaeri Jumaeri; Sri Kadarwati (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2021)
Diclofenac sodium is a non-steroidal anti-inflammatory drug with a relatively short release time. This short release time promotes a more frequent drug consumption and could lead to side effects in the stomach, e.g., gastrointestinal disorders, gastrointestinal bleeding, and gastric ulcers. A drug delivery system with a slow-release activity is one of the promising technologies to control the drug amount released to the stomach. A surfactant-modified natural zeolite as a carrier for diclofenac sodium has been used in this study. This study focused on the preparation, characterization, and slow-release performance of HDTMA-modified natural zeolite as a carrier for diclofenac sodium. The zeolite underwent chemical and physical activation, as well as milling prior to use. It was proven that the zeolite used was dominated by mordenite and clinoptilolite with high stability properties towards acid treatments, as indicated by the XRD patterns. A modification of the zeolite surface using HDTMABr was also successfully performed, indicated by the appearance of peaks at wavenumbers of 2923.05 cm-1 and 2853.39 cm-1 (symmetrical and asymmetrical CH2 strains of HDTMA molecules, respectively) in the FTIR spectra. The synthesized HDTMA-modified natural zeolite also showed an excellent surface property such as surface area, pore-volume, and size, as indicated by the BET-BJH isotherms on the nitrogen adsorption. The slow-release performance of the zeolite-based drug delivery system was studied by investigating the adsorption-desorption behavior of HDTMA-modified zeolite towards diclofenac sodium. The HDTMA-modified zeolite adsorbed the diclofenac sodium of 54.01% at a pH of 7.5, the contact time of 60 min, and the initial concentration of 100 ppm. The adsorbed diclofenac sodium of 73.95% could be released from the HDTMA-modified adsorbent for 8 h, mimicking the time length of drug metabolism in the human body.